COMMUNICATION AS THE BASIS OF PSYCHOLOGICAL AND PEDAGOGICAL INTERACTION OF THE EDUCATIONAL PROCESS SUBJECTS - Slobodianyk, Natalia (PSYCHOLOGICAL JOURNAL, 2018)
The author analyzes results of a theoretical research of the problem of communication role actualization as the basis of psychological and pedagogical interaction. Based on the use of methods of scientific analysis of the developed theories on communication problems, the main functions of pedagogical communication are revealed, groups of teachers are distinguished in terms of the intensity of their communication with pupils. Pedagogical communication is considered as a professional communication between the teacher and all participants of the educational process aimed at creating optimal conditions for the implementation of goal, objectives of upbringing and education. Professional pedagogical communication provides for its high psychological culture that gives evidence of the ability of the teacher to realize its potential in communication with other people, the ability to perceive, assimilate and transmit the contents of thoughts, feelings and aspirations in the process of education and upbringing. The leading role of the teacher in pedagogical communication is determined. It is emphasized that successful pedagogical communication in the process of interaction between the teacher and pupils requires certain psychological qualities and abilities from him. Among indicators of the personal plan, communicative aptitudes, abilities, knowledge and skills are of the greatest importance. The effectiveness of pedagogical communication is influenced by such indicators of the individual-personal plan as interests, level of preparation, habits of the teacher and pupil. The main component of pedagogical communication is emotional experiences. The key role of speech as the main means of pedagogical communication is substantiated in the article, types of interpersonal pedagogical interaction, styles of pedagogical communication are analyzed. The peculiarities of communication between the teacher and pupil at the level of subject-subject relations are considered. Key words: communication, pedagogical communication, professional communication, styles of communication, psychological and pedagogical interaction, pedagogical process, types of interaction, subjects of interaction.